Distance learning and patient safety: Report and evaluation of an online patient safety course - Johis Ortega; Maria Cristina Cometto; Rosa A. Zárate Grajales; Silvina Malvárez; Silvia Cassiani; Carmen Falconi; Daniel Friedeberg; Nilda Peragallo-Montano (Pan American Health Organization, 2020)
Patient safety is a critical topic in health care globally, with implications for nurses, physicians, administrators, and most importantly, patients and their well-being. Online distance learning (ODL) is widely accepted among most disciplines in higher education and has been used to promote patient safety knowledge among health care students and professionals in diverse contexts. This article reports on an online Nursing and Patient Safety course developed in 2012 by the University of Miami School of Nursing and Health Studies in conjunction with the Pan American Health Organization and the International Network for Nursing and Patient Safety. The study's objectives are to describe the implementation of an international ODL program to enhance patient safety knowledge in nurses and nursing students, and to examine the participants' assessments of this online approach as an effective learning tool. Most participants who completed the Nursing and Patient Safety ODL course reported being satisfied with the course content and experience, and demonstrated increased knowledge on patient safety, as measured by post-module quizzes and self-report. Limitations of the study include the lack of a comparison group, disparity in the number of participants across the course's language formats (English, Portuguese, Spanish), and the large number of participants who registered for but did not complete the course. Future research should identify obstacles to course completion, explore participants' awareness of patient safety issues and perceived need for more instruction, and look at ways to disseminate the course to the broadest international population of nurses and nursing students.